2011
DOI: 10.1260/0263-6174.29.9.887
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of Silver Ions by Paecilomyces Lilacinus Biomass: Equilibrium, Kinetics and Thermodynamics

Abstract: ABSTRACT:The freeze-dried biomass of Paecilomyces lilacinus was employed as a biosorbent for the removal of silver ions from aqueous solution. The effects of factors such as the solution pH, the initial Ag(I) ion concentration, contact time and temperature were examined. Maximum Ag(I) adsorption was obtained at pH 3.0. The pseudo-first-order, pseudo-second-order and intra-particle diffusion kinetic models were fitted to the experimental data when it was found that such data were best fitted by the pseudo-secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“… Yildirim et al (2020) utilized Pleurotus ostreatus powder for Ni (II) adsorption and observed a redshift in the absorption peak of -OH (-NH) from 3275 to 3369 cm –1 , consistent with our findings. Ou employed Paecilomyces lilacinus for Ag (I) adsorption and detected redshifts in the -OH peak from 3297 to 3304 cm –1 , blueshifts in the -CH peak from 2928 to 2926 cm –1 and in the -C = O peak from 1653 to 1652 cm –1 ( Ou et al, 2011 ). These alterations in functional groups align with our study’s findings.…”
Section: Resultsmentioning
confidence: 99%
“… Yildirim et al (2020) utilized Pleurotus ostreatus powder for Ni (II) adsorption and observed a redshift in the absorption peak of -OH (-NH) from 3275 to 3369 cm –1 , consistent with our findings. Ou employed Paecilomyces lilacinus for Ag (I) adsorption and detected redshifts in the -OH peak from 3297 to 3304 cm –1 , blueshifts in the -CH peak from 2928 to 2926 cm –1 and in the -C = O peak from 1653 to 1652 cm –1 ( Ou et al, 2011 ). These alterations in functional groups align with our study’s findings.…”
Section: Resultsmentioning
confidence: 99%
“…The ability to capture heavy metals by various microorganisms and biopolymers has been reported, whereas bacteria, yeasts, fungi, algae and industrial and agricultural wastes appear as good candidates for removal of these metals. Thus, biosorption process has also been exploited for the selective recovery of more valuable metals (Amirnia et al., 2012; Das and Das, 2014; Ou et al., 2011). The process proceeds through interactions between the metal species and the active sites (carboxyl, amino, sulfate) present on the outer surface of the cell wall of biomass.…”
Section: Introductionmentioning
confidence: 99%